Action Research and Language Teaching: From the Positioning of the Researcher to a Research Position - Macaire, Dominique (Rastros Rostros, 2015)
Research in didactics of languages and cultures finds its place as a field of research to the extent that it is recognized in every sense of the words that name it, something that is far from occurring in contemporary scientific thought. In fact, the didactics of languages suffers from a credibility deficit, which can be seen in its difficulty to position in the bosom of disciplines. In addition, the didactics of languages is not assumed as a science, but as a field that takes resources from the human and the language learner, usually in an institutional context. In short, it lives by its relationships with related sciences such as sociolinguistics or psycholinguistics, which nourishes didactics and is enriched by it. The didactics of languages and cultures (ddlc) deals with acquisitions and compares them with the learning of languages in different environments and, although these areas are hermetic, allow various appropriations by the individual of a multilingual and multicultural heritage.
Keywords: didactics of languages and cultures; action research; research methodology